Dampak Tradisi Ritual Adat Seblang Terhadap Perekonomian Masyarakat di Desa Olehsari Kabupaten Banyuwangi - Biati, Lilit; Mamlukhah, Mamlukhah; Suprapto, Ribut (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
The Seblang traditional ritual held in the Olehsari village is a tradition that has been carried out for generations by the people of the Olehsari village. This ritual is held every year to clean the village and repel reinforcements that require offerings of agricultural and plantation products. The aim of the research is to find out whether Seblang traditional rituals can influence the economic income of the Olehsari village community? This research method is descriptive qualitative and the results of this research are that seblang dancers must be descendants of previous dancers. The discussion is that the seblang ritual process begins with a charmer who is also a local traditional figure who places a special crown called omprog on the seblang dancer. In conclusion, the Seblang traditional ritual is the culture of the Sari community which believes that the word SEBLANG is a combination of the words SEBELE ILANG.